2010
DOI: 10.1002/cssc.200900224
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Selective Dehydration of Fructose to 5‐Hydroxymethylfurfural Catalyzed by Brønsted‐Acidic Ionic Liquids

Abstract: The dehydration of D‐fructose and glucose has been studied with acidic ionic liquids as catalysts. A series of Brønsted‐acidic ionic liquids has been synthesized and tested in the dehydration of D‐fructose. The results showed that N‐methyl‐2‐pyrrolidonium methyl sulfonate [NMP]+[CH3SO3]− and N‐methyl‐2‐pyrrolidonium hydrogen sulfate [NMP]+[HSO4]− have high catalytic activity. Highly efficient and selective dehydration of D‐fructose to 5‐hydroxymethylfurfural (HMF) was achieved in dimethyl sulfoxide (DMSO) unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(144 citation statements)
references
References 38 publications
4
139
0
1
Order By: Relevance
“…Aprotic media have been tested for LA synthesis, such as dimethylsulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMA), tetrahydrofuran (THF), methyl isobutyl ketone (MIBK), carbon tetrachloride, acetonitrile and ethyl acetate. DMSO is particularly selective towards 5-HMF because it suppresses the subsequent hydrolysis of 5-HMF to LA and formic acid [2,82]. Regarding aprotic solvents, Sanborn reported the synthesis of LA from fructose sources using a polyethylene glycol and an end capped polyethylene glycol together with an acid catalyst, in the presence of polar aprotic solvents, such as 1-methyl-2-pyrrolidone, dimethylacetamide, dimethylformamide, dimethylsulfoxide, methyl ethyl ketone, methyl isobutylketone, acetonitrile and propionitrile.…”
Section: Homogeneous and Heterogeneous Catalysts In Organic Solventsmentioning
confidence: 99%
“…Aprotic media have been tested for LA synthesis, such as dimethylsulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMA), tetrahydrofuran (THF), methyl isobutyl ketone (MIBK), carbon tetrachloride, acetonitrile and ethyl acetate. DMSO is particularly selective towards 5-HMF because it suppresses the subsequent hydrolysis of 5-HMF to LA and formic acid [2,82]. Regarding aprotic solvents, Sanborn reported the synthesis of LA from fructose sources using a polyethylene glycol and an end capped polyethylene glycol together with an acid catalyst, in the presence of polar aprotic solvents, such as 1-methyl-2-pyrrolidone, dimethylacetamide, dimethylformamide, dimethylsulfoxide, methyl ethyl ketone, methyl isobutylketone, acetonitrile and propionitrile.…”
Section: Homogeneous and Heterogeneous Catalysts In Organic Solventsmentioning
confidence: 99%
“…On the other hand, cellulose was dissolved easily in other systems, but the hydrolysis was hindered with the increase amount of NMP. It was reported that H 2 SO 4 can react with NMP to form a new acidic ionic liquids [NMP] þ [HSO 4 ] À [30]. Therefore, the actual proton used for catalyzing the cellulose hydrolysis became less with the increase amount of NMP.…”
Section: Effect Of Acids Loading On Cellulose Hydrolysis In [Bmim]cl/mentioning
confidence: 99%
“…• C for 20 h. In a round bottom flask, 1.4 g of SiO 2 NPs were dispersed in dry toluene. After the addition of 0.7 g of IL-HSO 4 the mixture was stirred under nitrogen atmosphere at 90.0 ± 2.0…”
Section: Immobilization Of Il-hso 4 Onto Nanoparticles Surfacesmentioning
confidence: 99%